Prognostic and predictive molecular biomarkers in colorectal cancer - Zhang, Jianzhi; Zhu, Hao; Liu, Wentao; Miao, Ji; Mao, Yonghuan; Li, Qiang (Frontiers in Oncology, 2025)
Precision medicine has brought revolutionary changes to the diagnosis and treatment of cancer patients, and is currently a hot and challenging research topic. Currently, the treatment regimens for most colorectal cancer (CRC) patients are mainly determined by several biomakers, including Microsatellite Instability (MSI), RAS, and BRAF. However, the roles of promising biomarkers such as HER-2, consensus molecular subtypes (CMS), and circulating tumor DNA (ctDNA) in CRC are not yet fully clear. Therefore, it is urgent to explore the potential of these emerging biomarkers in the diagnosis and treatment of CRC patients. In this paper, we discuss recent advances in CRC biomarkers, especially clinical data, and focus on the roles of biomarkers in prognosis, prediction, treatment strategies, and the intrinsic connections with clinical pathological features, hoping to promote better precision medicine for colorectal cancer.